Trends and Comparison of Children Hospitalized for Retropharyngeal and Parapharyngeal Abscesses 2003‐2009. (23rd August 2013) - Smith, Aaron M.; Cash, Elizabeth; Myers, John; Smith, Michael; Navale, Suparna; Woods, Charles; Chandran, Swapna K.
Abstract : Objectives: Following the peritonsillar space, two confluent spaces house the majority of pediatric deep neck space infections, the retropharyngeal and parapharyngeal sites. Surgical drainage and conservative antibiotic management exist as treatment options. Methods: We queried the Kid Inpatient Database identifying all cases of International Classification of Disease, ninth revision, clinical modification (ICD‐9‐CM) codes 478.22, parapharyngeal abscess (PPA), and 478.24, retropharyngeal abscess (RPA) for 2003, 2006, and 2009. Comparisons were made between population level estimates using Statistical Analysis Software. Results: The incidence (0‐20yo) of both RPA (0.67 to 0.81/100000population) and PPA (1.46 to 1.84/100000) increased slightly. Males were more likely than females to be afflicted (60% vs 40%). The median age for RPA was younger (4yo vs 5yo, P < 0.001). Median total charges increased (for RPA 12217 to 14453, P <0.01, for PPA 13184 to 19177, P < 0.01) with no cost difference between them ( P = 0.055). Median length of stay (LOS) remained constant (3 d). Surgical drainage occurred more often for PPA (43% vs 37%, P < 0.01); however, LOS increased when an RPA was surgically drained (4 vs 3 days, P < 0.01). Conclusions: These national population‐based estimates show a similar demographic stratification for RPA and PPA. Incidence has increased slightly with RPA occurring more often and at a younger age. Costs per hospitalization increased, but lengths of stay were constant. Surgery occurred more often for PPA but increased LOS for RPA. Surgery increased overall costs; however, cost and resource use were similar for both infections.